Recombinant thermostable maltogenic amylase from Geobacillus sp. Sk70 and its variants - Sulong, Moohamad Ropaning (2015)
A thermostable maltogenic amylase-producing bacterium was successfully isolated from a hot spring located at Sungai Klah, Perak, at 70°C. The 16S rRNA gene sequence showed 99% similarity to Geobacillus sp. and was deposited in the GenBank with the accession number JN812978. A 1767 bp gene was successfully amplified and was cloned into pGEM-T cloning vector. The gene encodes for the extracellular enzyme revealed 97% identical to maltogenic amylase of Geobacillus sp. Gh6, α- cyclodextrinase of Thermus sp. YBJ-1 and Geobacillus stearothermophilus, and α- amylase of Geobacillus sp. Y412MC61. The gene was effectively expressed in E. coli BL21 (DE3) using pET102 Directional TOPO expression vector and showed highest specific activity of the intracellular enzyme (61 U/mg) after 12 h of post induction time using 0.02 mM IPTG at OD600 0.5. Hence, the isolate was suggested as thermostable maltogenic amylase-producing Geobacillus sp. SK70 and was considered as the first ever to be expressed intracellularly using the pET102 Directional TOPO expression vector. The intracellular enzyme was purified to homogeneity with 8.2 fold and 41% recovery through a single step purification using HisTrap HP affinity column chromatography. The optimum temperature and pH for the purified enzyme was at 55°C and pH 7.0 respectively, and showed broad range of pH stability ranging from pH 5.0 to pH 10.0. The activity of the purified enzyme was stable in the presence of 1 mM Ca2+ , was enhanced by 1 mM Zn2+ and 0.1 % (v/v) Tween-20, and was 20% inhibited by 1% (v/v) of 2-Mercaptolethanol, EDTA and SDS. Thus, the enzyme is considered as Ca2+ - independent that differs to most of reported maltogenic amylases. Two single point mutations at positions Q294H and A550K were conducted to enhance the thermostability of the wild-type enzyme. The mutant Q294H revealed optimum temperature at 60°C as compared to the mutant A550K and the wild-type enzyme that showed optimum temperature at 55°C. The half-life of the mutant Q294H was found to be 85 min comparing to 35 min of the wild-type enzyme and retained almost 80% of the enzyme activity in the presence of 1 mM of Mg2+, Ca2+and Fe2+ , and was not significantly affected by detergents, reducing agents and additives. Interestingly, the enzyme activity was enhanced by 1 mM Mn2+ and 0.1 % (v/v) Tween-20, thus demonstrated characteristic unlike other reported maltogenic amylases. To study the effect of mutation on thermostability of the mutant enzymes, molecular dynamic (MD) simulation of both wild-type and mutant enzymes for 20 ns at 60°C was performed. The root mean square deviation (RMSD) for both wild-type and mutant enzymes showed no significant structural alteration has occurred. The relatively minor difference in radius of gyration (Rg) would provide a better structure compactness to the mutants. While lower solvent accessible surface area (SASA) value for the mutant Q294H comparing to the mutant A550K and the wild-type enzyme indicated the mutant Q294H would have better protein folding and subsequently would give better enzyme thermostability. The circular dichroism (CD) spectra analysis for both mutant enzymes showed characteristic differences in their secondary structure as compared to the wild-type enzyme. Higher percentage of β-sheets (23.6%) than α-helices (16.7%) in the mutant Q294H comparing to the mutant A550K and the wild-type enzyme has given more stability to the protein folding. While higher melting temperature for mutant Q294H (79.31°C) as compared to the mutant A550K (41.66°C) and the wild-type enzyme (53.3°C) has offered good characteristics for industrial applications. The results of the study of both wild-type enzyme and mutant Q294H demonstrated that these enzymes can be applied in various industrial sectors including foods industry and enzyme enriched detergent formulations. Further research for large scale production of mutant Q294H is recommended. Besides, the uniqueness of amylases produced by the other four isolates also should be further investigated.